Prevalence and possible complications of pediatric obesity in Romania: A review of recent literature - Cristina Ramona Radulescu; Ioana Adriana Ghiorghiu; Doina Anca Plesca (Amaltea Medical Publishing House, 2020)
Introduction. Excess weight has been recognized as a global health issue for many years. It is an established risk factor for several chronic conditions, notably cardiovascular disease and diabetes, and is increasingly present in the pediatric population. The purpose of this paper is to review the existent local data regarding pediatric excess weight (including obesity) and its impact. Method. A review of existent literature from the year 2000 and onwards was performed. Only material referring to a Romanian cohort (or subgroup) was included. Results. Of the initial 455 identified records, 62 full text papers in English and Romanian were considered relevant to the topic and analyzed. A mean prevalence of excess weight of 31.6% (WHO), 18.35% (CDC) and 21.37% (IOTF) with obesity rates of 11.4% (WHO), 7.2% (CDC) and 7.69% (IOTF) was calculated. Several factors that could promote excess weight have been identified in Romanian cohorts and are presented. Possible complications are in line with previous published data and mainly involve the cardiovascular system and metabolic effects. Psychological obesity-associated issues have also been reported. Discussion. To our knowledge, there has not been a local study to assess the prevalence of pediatric excess weight at a country level. The available prevalence data is in line with both previous reports of Romanian data and international figures. There does not appear to be an increase in rates over time in the last few years. Systematic country-level attempts to tackle the excess weight problem are few, however smaller range community based intervention programs have been reported, with modest results. Conclusions. A worrying proportion of children are overweight or obese in Romania and this may lead to a variety of physical and psychological issues for the child. Conditions such as arterial hypertension and dyslipidemia, typically encountered in adults, are being noted with increased frequency in the pediatric population and their full impact on quality of life and life expectancy is difficult to grasp. Sustained, community-based interventions could possibly achieve a slow reduction in the rates of pediatric excess weight.